2006
DOI: 10.1590/s0074-02762006000200013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bulgarian propolis against Trypanosoma cruzi and during its interaction with host cells

Abstract: Propolis has shown activity against pathogenic microorganisms that cause diseases in humans and animals. The ethanol (Et-Blg) and acetone (Ket-Blg) extracts from a Bulgarian propolis, with known chemical compositions, presented similar activity against tissue culture-derived amastigotes. The treatment of Trypanosoma cruzi-infected skeletal muscle cells with Et-Blg led to a decrease of infection and of the intracellular proliferation of amastigotes, while damage to the host cell was observed only at concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
1
34
0
1
Order By: Relevance
“…Additional experiments with BRG and BRPG samples were abandoned because at concentrations higher than 25 µg/ml both extracts were toxic to macrophages. In fact some studies have demonstrated propolis toxicity for different cell types (Higashi & de Castro 1994, Chen et al 2001, Ferguson 2001, Dantas et al 2006, Tavares et al 2006. For example, damage to murine macrophages was observed after treatment with ethanolic extract of propolis at concentrations above 30 µg/ml (Higashi & de Castro 1994), and genotoxic effect of ethanolic extract of Brazilian propolis (100 µg/ml) was detected in Chinese hamster ovary cells (Tavares et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional experiments with BRG and BRPG samples were abandoned because at concentrations higher than 25 µg/ml both extracts were toxic to macrophages. In fact some studies have demonstrated propolis toxicity for different cell types (Higashi & de Castro 1994, Chen et al 2001, Ferguson 2001, Dantas et al 2006, Tavares et al 2006. For example, damage to murine macrophages was observed after treatment with ethanolic extract of propolis at concentrations above 30 µg/ml (Higashi & de Castro 1994), and genotoxic effect of ethanolic extract of Brazilian propolis (100 µg/ml) was detected in Chinese hamster ovary cells (Tavares et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in products like "healthy foods" and "biocosmetics" (Marcucci & Bankova 1999). Many authors have reported the in vitro activities of propolis against different microorganisms, among them some important human pathogens, such as Staphylococcus aureus, Salmonella thyphimurium, Candida albicans, Trypanosoma cruzi, and Giardia duodenalis (Higashi & de Castro 1994, Marcucci et al 2001, Miorin et al 2003, Uzel et al 2005, Dantas et al 2006, Freitas et al 2006, Trusheva et al 2006. Brazilian propolis is the subject of an intensive study of chemists, biologists, and physicians all over the world due to specific tropical flora and their different chemical components (Marcucci & Bankova 1999, Marcucci et al 2001, Trusheva et al 2006.…”
mentioning
confidence: 99%
“…Some previous studies have demonstrated the therapeutic potential of compounds derived from natural sources. 16,[48][49] Several synthetic compounds have also shown trypanocidal activity. 50,51 Acanthoic acid (1) at 3 µmol L -1 (the lowest concentration tested) displayed a growth inhibition of parasites of 13.6%, while at the highest concentration (331 µmol L -1 ), over 90% of the cells were affected.…”
Section: Biological Studiesmentioning
confidence: 99%
“…its antimicrobial properties are the most often studied and there are numerous articles proving the action of Bulgarian bee glue against bacteria (6,17,42), incl. Helicobacter pylory (10,11) and Salmonella (36); anti-influenza virus activity (29,43), antiparasitic activity against Tripanozoma cruzii (12,40) and Leishmania (28). the immunomodulatory activity of Bulgarian propolis has also been reported (13,14,15).…”
Section: Bulgarian Propolismentioning
confidence: 99%